Determination of polar organic micropollutants in surface and pore water by high-resolution sampling-direct injection-ultra high performance liquid chromatography-tandem mass spectrometry. Issue 12 (23rd October 2018) - Posselt, Malte; Jaeger, Anna; Schaper, Jonas L.; Radke, Michael; Benskin, Jonathan P.
Abstract : A new method was developed for in situ characterization of polar organic micropollutants in hyporheic pore water at high spatial and temporal resolution. Abstract : Hyporheic zones (HZs) are dynamic and complex transition regions between rivers and aquifers which are thought to play an important role in the attenuation of environmental micropollutants. Non-steady state and small-scale hyporheic processes which affect micropollutants in the HZ are poorly characterized due to limitations in existing analytical methodologies. In this work we developed a method for high spatio-temporal resolution analysis of polar organic micropollutants (POMs) in hyporheic pore- and surface waters by combining (semi-) automatic low volume sampling techniques with direct-injection ultra-high performance liquid chromatography tandem mass spectrometry. The method is capable of quantifying 25 parent compounds and 18 transformation products (TPs) using only 0.4 mL of water and few preparation steps. Application of the method to both surface and pore water revealed significant ( i.e. > an order of magnitude) differences in POM concentrations over small time and spatial scales ( i.e. < a few hours and tens of cm, respectively). Guanylurea, a TP of the antidiabetic drug metformin was detected at unprecedentedly high concentrations. Collectively, this method is suitable for in situ characterization of POMs at high spatial and temporal resolution and with minimal disturbance of natural flow paths and infiltration of surface water.